Lasso de la Vega and the CDU: an incessant controversy - Blanco Domingo, Luis Mariano (Revista General de Información y Documentación, 2021)
This work tries to deepen the misgivings that the implantation and development of the CDU in Spain supposed, discrepancies sometimes derived from personal, professional or ideological disagreements rather than exclusively technical aspects. Throughout three fundamental chronological milestones (la Guerra Civil, the 1950s and La Transición), he reconstructs the constant efforts of Javier Lasso de la Vega for his settlement and generalization.